Moderasi beragama di Indonesia dalam kajian literatur tentang konsep, prinsip, dan dinamika implementasinya - Ahmad Nur Wahid; April Adit Sugiarto; Afrin Jaya Pradwita; Helen Diantini; Intan Myluna Izza; Kayla Zahy’ra Setiawan; Rensi Rima Yasinta; Rika Nur Aini Rika Nur Aini; Salman Fariz Az-zaki (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
Indonesia is a multicultural nation characterized by a high level of religious, ethnic, and cultural diversity. Within this context of pluralism, the potential for conflict arising from differences in religious understanding, intolerance, and radicalism remains a significant challenge. This study aims to examine the concept of religious moderation (wasathiyah) in Islam, explore the Islamic perspective on the existence of non-Muslims, and identify forms of inclusive interaction in social life and their implications for education. The study employs a descriptive qualitative approach based on library research by analyzing relevant literature, documents, and religious texts. The findings reveal that religious moderation in Islam encompasses four major dimensions: faith (aqidah), worship (ibadah), morality (akhlaq), and the formulation of Islamic law (tasyri’). In dealing with non-Muslims, Islam emphasizes the principles of tasamuh (tolerance), al-insaniyyah (humanity), and proportional justice, which were historically exemplified through the Constitution of Medina. Interactions between Muslims and non-Muslims are manifested inclusively in social (muamalah), economic, educational, and humanitarian spheres while maintaining the theological boundaries of each faith. Religious moderation plays a strategic role in fostering harmony, stability, and peaceful coexistence in Indonesia. Therefore, the internalization of moderation values through educational institutions is an urgent necessity to cultivate a tolerant, inclusive, and socially responsible younger generation.